2018
DOI: 10.1016/j.physleta.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the deGennes extrapolation parameter on the resistive state of a superconducting strip

Abstract: We studied the resistive state of a mesoscopic superconducting strip (bridge) at zero external applied magnetic field under a transport electric current, J a , subjected to different types of boundary conditions. The current is applied through a metallic contact (electrode) and the boundary conditions are simulated via the deGennes extrapolation length b. It will be shown that the characteristic current-voltage curve follows a scaling law for different values of b. We also show that the value of J a at which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
(46 reference statements)
0
9
0
1
Order By: Relevance
“…At a certain value of J a , there is an inversion where the kinematic vortices nucleate; they are formed at the edges and then are annihilated at the center phase R-II. The two resistive phases are delimited by the local maximum of the I-R curve, as we stated previously [4,5].…”
Section: The Vortex Dynamicsmentioning
confidence: 69%
See 3 more Smart Citations
“…At a certain value of J a , there is an inversion where the kinematic vortices nucleate; they are formed at the edges and then are annihilated at the center phase R-II. The two resistive phases are delimited by the local maximum of the I-R curve, as we stated previously [4,5].…”
Section: The Vortex Dynamicsmentioning
confidence: 69%
“…This was first proposed by Andronov et al and later observed experimentally by Sivakov et al [1,2]. They consist of V-Av pairs that move at a much larger velocity than a normal Abrikosov vortex [1][2][3][4][5][6][7][8][9]. Several theoretical and experimental investigations have been performed on superconductors with defects in the presence of external applied transport currents.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…[7]. Fink et al studied the effect of the presence of another material in contact with the superconducting sample (simulated by ) [3,5] on for various geometries. They found that the deGennes parameter is useful to analyze the variation of T c in mesoscopic superconductors [8].…”
Section: Palabras Clavesmentioning
confidence: 99%